DINAMIKA CITRA CALON PRESIDEN RI 2024 DALAM KONTESTASI POLITIK - Syaifullah, Jahid; Agung Wibiyanto; Ali Arif Setiawan (Jurnal Ilmu Komunikasi Balayudha, 2024)
The political competition in Indonesia is quite dynamic and is also heating up towards 2024, especially from the competing candidates for the Indonesian presidency, such as Ganjar Pranowo, Prabowo Subianto and also Anies Baswedan. The purpose of this article is to review the dynamics of the image of the 2024 RI presidential candidate in political contestation. The method used is qualitative with descriptive analysis, where the data obtained is processed and reduced and analyzed to become an article. The findings state that the dynamics of the image of the 2024 Republic of Indonesia presidential candidate include personal images of Ganjar Pranowo, Prabowo Subianto and Anies Baswedan, images in issues of sustainability and issues of change, Anies Baswedan "held hostage" by identity politics, President Jokowi's legacy competition among sustainability groups, Ganjar's image as a barrier Pranowo as "party official", All Jokowi Mens, Prabowo Subianto's calm politics, battle between king makers, volunteer political pattern. Keywords: Image Dynamic, RI 2024 presidential candidate, Political Contest.